Biofilms of Candida albicans and Streptococcus sanguinis and their susceptibility to antimicrobial effects of photodynamic inactivation - Palma, Ana Luiza do Rosário [UNESP]; Paula-Ramos, Lucas de [UNESP]; Domingues, Nádia [UNESP]; Back-Brito, Graziella Nuernberg [UNESP]; de Oliveira, Luciane Dias [UNESP]; Pereira, Cristiane Aparecida [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Elsevier, 2018)
This study evaluated the effects of photodynamic inactivation (PDI) on single and multi-species biofilms, compounds by Candida albicans and Streptococcus sanguinis. Biofilms were formed, on microplate of 96 wells, by suspensions of C. albicans (ATCC 18804) and S. sanguinis (ATCC 7073) adjusted in 10 7 cells/mL, followed by incubation of 48 h (with 5% CO 2 ). The effects of the photosensitizer erythrosine (ER) at 400 μM for 5 min and green light-emitting diode (LED - 532 ± 10 nm) for 3 min, alone and conjugated, were evaluated. After normality test, results was analysed by Tukey´s test (P < 0.05). PDI group promoted reductions of 1.07 and 0.39 log 10 , respectively, in biofilms of C. albicans alone and in association with S. sanguinis. Biofilms of S. sanguinis alone were more sensitive, with reduction of 4.48 log 10 . When in association with the yeast, S. sanguinis have a decrease of 2.67 log 10 . SEM analysis revealed a decrease in bacterial and fungal structures of biofilms treated with PDI. In conclusion PDI promoted significant microbial reductions in both species of microorganisms grown on mixed biofilms. This study is one of the pioneers to evaluate the antimicrobial action of PDI on biofilms of S. sanguinis and C. albicans, demonstrating a way to control these microorganisms of clinical importance.
Keywords: Antimicrobial, Antimicrobial -Photodynamic Therapy; Biofilm; Candida albicans; Photodynamic inactivation; Streptococcus sanguinis